Studies on the biochemistry of insects. XVIII. Data on protein metabolism in the common bee (APIS MELLIFICA) (Revista Española de Fisiología, 1963)
Using Lowry’s photocolorimetric method and the paper electrophoretic method, a study has been made, on the common bee (Apis mollifica), of the soluble proteins and electrophoretic fractions appearing in the larvae and worker-bees, whereby it has been proved that the amount of proteins in the larvae is twice as high as that in the workers. In the latter we can detect three electrophoretic fractions for every four in the larvae, and of these one in the workers and two in the larvae are colourings of a greyish hue, which do not change their colour with bromophenol bine.